The mitigatory capabilities of exercise on breast cancer chemotherapy-induced cardiotoxicity - Qian, Chen-yue; Fan, Juan; Guo, Jing-yi; Li, Na; Liu, Xiang-qi; Liu, Xiu; Zeng, Xiang-yuan; Huang, Cui-feng; Li, Cong; Liu, Hua-dong; Liu, Jing-jin (Frontiers in Cell and Developmental Biology, 2025)
Chemotherapy drugs have significantly decreased breast cancer morbidity and mortality, but they have been associated with increased risk for adverse cardiovascular side effects, such as cardiotoxicity. These drugs generally fall under three broad categories: cell cycle inhibitors (ex. Anthracyclines, taxanes), human epidermal growth factor 2 (HER2) blockers (ex. Trastuzumab, pertuzumab), as well as other medications, such as the alkylating agent cyclophosphamide. This review analyzes the occurrence of specific cardiotoxic manifestations linked to increased heart failure risk, such as chest discomfort, edema, and dyspnea, as well as mechanisms of action, such as anthracycline inducing the generation of reactive oxygen species, for the aforementioned three drug categories. In particular, attention is given to anthracyclines and HER2 blockers, as they are two of the most commonly prescribed medications. On the other hand, the cardiotoxic effects of these medications have been found to be able to be mitigated by various exercise regimens, such as aerobic exercises, resistance training, and high intensity interval training. This review also examines the effectiveness of different regimens on alleviating post-chemotherapy cardiotoxicity in breast cancer patients, as well as the specific mechanisms involved, such as aerobic exercise being able to downregulate the expression of doxorubicin-induced pro-inflammatory factors (ex. Interleukin-8, cyclooxegenase-2, etc.). Moreover, the review points out the relative lack of cardiac rehabilitation programs specifically addressing the post-chemotherapeutic cardiotoxicity risks of breast cancer patients. Therefore, customized exercise regimens, accounting for breast cancer patient-specific medical profiles, should be developed to counteract against the adverse cardiovascular effects of chemotherapy.